Update to: Application of Bayesian decision-making to laboratory testing for Lyme disease and comparison with testing for HIV - Cook MJ; Puri BK (International Journal of General Medicine, 2017)
Michael J Cook,1 Basant K Puri21Independent researcher, Highcliffe, UK; 2Department of Medicine, Hammersmith Hospital, Imperial College London, London, UKIn our recent Bayesian analysis paper, false-negative results were compared between Lyme disease and HIV using a recommended test algorithm.1 When the two-tier test methodology for Lyme disease was compared with HIV two-stage testing, false negatives could be more than 500 times higher for Lyme disease testing.